(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT: Implementation of policies granting of micro and small enterprises aims to give consent to micro and small businesses for people who have small businesses and small that their enterprises have the legality / validity of the government, but in fact the service performed has not gone up, therefore, this study is intended to answer questions about how the implementation of policies granting of micro and small enterprises. In this study, researchers used a model of implementation of the George C. Edward III, where the implementation level visits from four aspects which have great impact in policy implementation. Communication is an aspect for the government to inform policy to the public as target group. Adequate resources both human resources and financial resources will affect the success rate policy. Disposition is the attitude held by implementing policies such as ethics and commitment to make this policy succeed. The bureaucratic structure is the operational structure of the mechanisms of services and organizational structure of the implementing agency policies. In this research using descriptive qualitative research method is through interviews with 10 informants, direct observation and document searches in connection with the policy, even in research assisted by the interview, a tape recorder and stationery menulis.Hasil research in general explained that the Implementation Granting Policy for Micro And Small at the District Office Malalayang has not gone up. Keywords: Policy Implementation, License Micro And Small